Active tuning of stroke-induced vibrations by tennis players - Chadefaux, D.; Rao, G.; Androuet, P.; Berton, E.; Vigouroux, L. (Journal of Sports Sciences, 2017)
This paper investigates how tennis players control stroke-induced vibration. Its aim is to characterise how a tennis player deals with entering vibration waves or how he/she has the ability to finely adjust them. A specific experimental procedure was designed, based on simultaneously collecting sets of kinematic, vibration and electromyographic data during forehand strokes using various commercial rackets and stroke intensities. Using 14 expert players, a wide range of excitations at spectral and temporal levels were investigated. Energetic and spectral descriptors of stroke-induced vibration occurring at the racket handle and at the player`s wrist and elbow were computed. Results indicated that vibrational characteristics are strongly governed by grip force and to a lower extent by the racket properties. Grip force management drives the amount of energy, as well as its distribution, into the forearm. Furthermore, hand-grip can be assimilated to an adaptive filter which can significantly modify the spectral parameters propagating into the player`s upper limb. A significant outcome is that these spectral characteristics are as much dependent on the player as on the racket. This contribution opens up new perspectives in equipment manufacture by underlining the need to account for player/racket interaction in the design process.